Cotton-textile-apparel sectors of India - Bedi, Jatinder S.; Cororaton, Caesar B. (International Food Policy Research Institute, 2008)
Cotton, textiles, and apparel are critical agricultural and industrial sectors in India. This study provides descriptions of these sectors and examines the key developments emerging domestically and internationally that affect the challenges and opportunities the sectors face. More than four million farm households produce cotton in India, and about one-quarter of output is produced by marginal and small farms. Although production has expanded-most recently with the introduction of Bt (Bacillus thuringiensis) cotton-domestic prices dropped sharply in the late 1990s, in parallel to world cotton prices. Using partial equilibrium simulations, we estimate that a price movement of the magnitude that occurred has a significant effect on levels of poverty among cotton-producing households. The fiber-to-fabric production chain, from cotton processing through apparel, employs more than 12 million workers in India and provides 16 percent of export earnings. Except for the spinning industry, these sectors are dominated by small, fragmented, and nonintegrated units, which adversely affect their competitiveness. Recent policy reforms have induced some technological improvements. In terms of future prospects for the Indian processing, textile, and apparel industries, our analysis emphasizes three dimensions of reform: the need for further investments in human resource development to improve industry productivity and reduce poverty among workers in these sectors, the emergence of modern domestic retail marketing chains, and the potentially vibrant prospects for the industry that arise from a growing domestic fabric demand and new opportunities in world markets if appropriate policies and investments are undertaken.